Mitochondrial genome variant m.3250T>C as a possible risk factor for mitochondrial cardiomyopathy. Issue 2 (1st December 2020) - Campbell, Teresa; Lou, Xiaoting; Slone, Jesse; Brown, Jenice; Bromwell, Meghan; Liu, Jie; Bai, Renkui; Haude, Katrina; Balog, Amanda; Cui, Hong; Zou, Weiwei; Yang, Li; et al.
Abstract: The MT‐TL1 gene codes for the mitochondrial leucine transfer RNA (tRNA Leu(UUR) ) necessary for mitochondrial translation. Pathogenic variants in the MT‐TL1 gene result in mitochondriopathy in humans. The m.3250T>C variant in the MT‐TL1 gene has been previously associated with exercise intolerance and mitochondrial myopathy, yet disease classification for this variant has not been consistently reported. Molecular studies suggest the m.3250T>C variant does not alter tRNA Leu(UUR) structure but may have a modest impact on aminoacylation capacity. However, functional studies are limited. Our study aimed to further define the clinical presentation, inheritance pattern, and molecular pathology of the m.3250T>C variant. Families with the m.3250T>C variant were recruited from the Mitochondrial Disease Clinic at Cincinnati Children's Hospital Medical Center and GeneDx laboratory database. Affected individuals most frequently presented with cardiac findings, exercise intolerance, and muscle weakness. Hypertrophic cardiomyopathy was the most frequent cardiac finding. Many asymptomatic individuals had homoplasmic or near homoplasmic levels of the m.3250T>C variant, suggesting the penetrance is incomplete. Patient‐derived fibroblasts demonstrated lowered ATP production and increased levels of reactive oxygen species. Our results demonstrate that the m.3250T>C variant exhibits incomplete penetrance and may be a possible cause of cardiomyopathy by impacting cellular respiration in mitochondria. Abstract :